1983
DOI: 10.1002/tera.1420280307
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of dietary zinc, genetic strain, and acetazolamide in teratogenesis in mice

Abstract: The effect of dietary zinc and genetic strain on acetazolamide-induced malformations was assessed. CBA (sensitive) and SWV (resistant) mice were fed purified diets containing five different levels of zinc throughout gestation and were given acetazolamide orally for a limited period during organogenesis. Controls received either no treatment or the drug vehicle. Litters were assessed for resorptions and malformations at term. The significance for influencing litter outcome was tested for the three main treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…While the concept that APR-induced changes in maternal-fetal zinc metabolism might represent a common mechanism contributing to the teratogenicity of a wide variety of toxicants and environmental insults has received considerable support, it still must be viewed as a hypothesis. Regardless, it is exciting to consider the possibility that this concept could help to explain the observation that the teratogenicity of diverse agents ranging from thalidomide (Jackson and Schumacher, 1979), acetazolamide (Hackman and Hurley, 1983), alcohol (Carey et al, 2003b;Miller et al, 1983), salicylate (Hackman and Hurley, 1984), and 6-MP (Amemiya et al, 1986) to alpha-hederin Duffy et al, 1997), can be modulated by the mother's intake of dietary zinc. From a larger perspective, this might provide one explanation for why women who consume ''poor diets'' have an elevated risk for pregnancy complications, as it would suggest that such women would have an increased sensitivity to teratogenic insults that trigger an APR.…”
Section: Secondary Deficiencies Of Zincmentioning
confidence: 97%
“…While the concept that APR-induced changes in maternal-fetal zinc metabolism might represent a common mechanism contributing to the teratogenicity of a wide variety of toxicants and environmental insults has received considerable support, it still must be viewed as a hypothesis. Regardless, it is exciting to consider the possibility that this concept could help to explain the observation that the teratogenicity of diverse agents ranging from thalidomide (Jackson and Schumacher, 1979), acetazolamide (Hackman and Hurley, 1983), alcohol (Carey et al, 2003b;Miller et al, 1983), salicylate (Hackman and Hurley, 1984), and 6-MP (Amemiya et al, 1986) to alpha-hederin Duffy et al, 1997), can be modulated by the mother's intake of dietary zinc. From a larger perspective, this might provide one explanation for why women who consume ''poor diets'' have an elevated risk for pregnancy complications, as it would suggest that such women would have an increased sensitivity to teratogenic insults that trigger an APR.…”
Section: Secondary Deficiencies Of Zincmentioning
confidence: 97%
“…Interestingly, acetazolamide‐induced postaxial forelimb ectrodactyly is heavily dependent on zinc status. Lowering dietary zinc increases the frequency of offspring with postaxial forelimb ectrodactyly at a constant dose of acetazolamide (Hackman and Hurley, 1983). Acetazolamide is a sulfonamide that acts pharmacologically through inhibition of carbonic anhydrase, a zinc metalloenzyme.…”
Section: Resultsmentioning
confidence: 99%
“…However, the incidence of malformations in the oyster-supplemented group was identical to the zinc-supplemented group (20 pprn Zn). With marginal zinc deficiency (4.5-10 pprn zinc), previous studies have shown low incidences of external malformations in mice (Hackman and Hurley, 1983;Sato et al, 1985). These findings suggest that zinc from the oyster extract may also have been absorbed effectively.…”
Section: Discussionmentioning
confidence: 99%